e-Bimbing Solat: The Development of Augmented Reality Digital Content to Enhance Learning Experience for Patients to Perform Prayers. - Ismail, Nurul Fatin Athirah; Abdul Rahman, Dina Safiah; Ahmad Zaini, Ainnur Diyanah; Mohamed Ali @ Md Hani , Mohd Hatta (Multidisciplinary Applied Research and Innovation, 2022)
Every Muslim is obliged to perform prayers in any situation, including when someone is sick. The method of performing prayers for the sick people is different. Since it is rarely practiced then we tend to seek information about it. Unfortunately, most of that information is not produced in digital content. Therefore, this study was conducted to find new methods that are more effective in knowledge delivery. Through the rapid development of digital technology, it has triggered the phenomenon of information search exploration more effectively. The use of mobile devices with the integration of Augmented Reality (AR) technology will further help patients' understanding in learning and performing prayers. Augmented Reality allows users to view 2D or 3D virtual objects projected against the real world. Next, this study also identifies the factors that can improve understanding in learning the method of prayer for a patient. It is hoped that the success of this study can also be applied in various fields and commercialized.